2012
DOI: 10.1016/j.healthplace.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood context and incidence of type 1 diabetes: The SEARCH for Diabetes in Youth Study

Abstract: Findings regarding type 1 diabetes mellitus (T1DM) and neighborhood-level characteristics are mixed, with few US studies examining the influence of race/ethnicity. We conducted an ecologic study using SEARCH for Diabetes in Youth Study data to explore the association of neighborhood characteristics and T1DM incidence. 2002–2003 incident cases among youth at four SEARCH centers were included. Residential addresses were geocoded to US Census Tract. Standardized incidence ratios tended to increase with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…This higher incidence of poor control DKA in children with lower socioeconomic status is consistent with previous studies . It is been suggested that a higher socioeconomic and educational level has higher incidence of T1DM; however, the findings in this and other studies show a higher rate of DKA admissions among population with the lowest socioeconomic level . African American children showed a significant higher mean Hb1Ac at the time of admission, which translates to a continuous poor glycaemic control; consistent with findings from previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…This higher incidence of poor control DKA in children with lower socioeconomic status is consistent with previous studies . It is been suggested that a higher socioeconomic and educational level has higher incidence of T1DM; however, the findings in this and other studies show a higher rate of DKA admissions among population with the lowest socioeconomic level . African American children showed a significant higher mean Hb1Ac at the time of admission, which translates to a continuous poor glycaemic control; consistent with findings from previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…4547 For example, a third to half of Hispanic and African American children seem to have a form of type 1 diabetes without islet autoantibodies, and with pancreatic histology showing a lack of islets and complete loss of β cells—ie, pseudoatrophic islets. 42 A 2011 study of adult-onset type 1 diabetes suggested that autoimmune type 1 diabetes in children and adults differs by just a few age-dependent genetic effects; 48 however, overall, type 1 diabetes seems to represent a heterogeneous disease whose pathogenic processes, genetics, and phenotypic characteristics show marked variation.…”
Section: Diagnosismentioning
confidence: 99%
“…Thus, together with individual-level sociodemographic factors, neighborhood-level factors may also increase the risk of many diseases. For example, neighborhood deprivation is associated with several cardiovascular risk factors; it has been shown to be an important independent risk factor for coronary heart disease and other cardiovascular diseases [13,14,15,16,17], psychiatric disorders [18], and certain specific types of ADs [19,20,21]. There is also a link between cardiovascular diseases and ADs [22].…”
Section: Introductionmentioning
confidence: 99%